1992
DOI: 10.3109/02656739209037979
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for intraoperative hyperthermia with ultrasound: the Dartmouth experience with 19 patients

Abstract: Over the course of 3 years, tumours of 19 patients were heated with ultrasound in the operating room during surgical resection. Immediately following intraoperative radiation therapy, thermocouples were inserted into tumour and adjacent normal structures. Patients were then given a 60-min heat treatment with ultrasound after a 10-15-min heatup period. Temperatures were measured at a total of 133 fixed locations for the 19 patient series. Temperature mapping was done in the tumour volume when logistically feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Ashayeri et al 18 reported a post-operative survivorship averaged up to 15.8 months for ®ve patients with unresectable pancreatic adenocarcinoma that were treated with simultaneous intra-operative radiotherapy and intra-operativ e hyperthermia. Ryan et al 17 studied 19 patients that were heated with ultrasound in the operating room during surgical resection. Immediately following intra-operativ e radiation therapy, thermocouples were inserted into the tumour and adjacent normal structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashayeri et al 18 reported a post-operative survivorship averaged up to 15.8 months for ®ve patients with unresectable pancreatic adenocarcinoma that were treated with simultaneous intra-operative radiotherapy and intra-operativ e hyperthermia. Ryan et al 17 studied 19 patients that were heated with ultrasound in the operating room during surgical resection. Immediately following intra-operativ e radiation therapy, thermocouples were inserted into the tumour and adjacent normal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Local IOHT has already been used, with quite promising results, without systemic toxicity [16][17][18] . Attempting to improve local control and patient's quality of life, one applied a new treatment modality using the combination of a single session local IOHT with intra-operative (intra-arterial ) chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, regardless of the surgical procedure, the radiation therapy technique, the type of chemotherapy and hormonal therapy, or the combinations thereof, the survival of pancreatic cancer patients remains low, with the major problem that of the local control of disease 10. Local intraoperative hyperthermia (IOHT) has already been used, with promising results, without systemic toxicity …”
Section: Introductionmentioning
confidence: 99%
“…Local intraoperative hyperthermia (IOHT) has been already used with quite promising results without systemic toxicity (Colacchio et al. 1990; Ryan et al. 1992; Ashayeri et al.…”
Section: Introductionmentioning
confidence: 99%
“…Local intraoperative hyperthermia (IOHT) has been already used with quite promising results without systemic toxicity (Colacchio et al 1990;Ryan et al 1992;Ashayeri et al 1993). The concept of combining hyperthermia with chemotherapy for pancreatic tumours was based on the well-known cell-killing properties of hyperthermia and on its synergistic effects with many chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%